KEPEMIMPINAN SEBAGAI PENUNJANG KARIR BAGI SISWA SMA - Reza Anshori; Muhammad Indra Gunawan (ICON Publisher, 2026)
Leadership is a crucial competency needed by individuals to support career development in various fields. A lack of understanding of the concept of leadership often leads to individuals being unable to develop their potential within the workplace or organization. This community service activity aims to improve participants' understanding of the concept of leadership and its role in supporting career development. The methods used in this activity include counseling and training, implemented through material delivery, discussions, and evaluation using pre- and post-tests. The activity was conducted with participants consisting of students and productive youth in the community. The results of the activity showed an increase in participants' understanding of the concept of leadership and the importance of leadership skills in career development. Through this activity, it is hoped that participants will be able to develop leadership skills as provisions for entering the workforce and improve the quality of their future careers.